A Poetics of Plot for the Twenty-First Century Theorizing Unruly Narratives - Richardson, Brian (The Ohio State University Press, 2019)
Story, in the largest sense of the term, is arguably the single most important aspect of narrative. But with the proliferation of antimimetic writing, traditional narrative theory has been inadequate for conceptualizing and theorizing a vast body of innovative narratives. In A Poetics of Plot for the Twenty-First Century: Theorizing Unruly Narratives, Brian Richardson proposes a new model for evaluating literature-returning to the basis of narrative theory to illuminate how authors play with and help clarify the boundaries of narrative theory. While he focuses on late modernist, postmodern, and contemporary narratives, the study also includes many earlier works, spanning from Aristophanes and Shakespeare through James Joyce and Virginia Woolf to Salman Rushdie and Angela Carter.